The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10545-012-9453-6
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for mevalonate shunting in moderately affected children with Smith‐Lemli‐Opitz syndrome

Abstract: Summary Smith-Lemli-Opitz syndrome (SLOS) is caused by a genetic deficiency in 7-dehydrocholesterol (7-DHC) reductase (EC 1.3.1.21), the last enzyme of the cholesterol synthetic pathway. In SLOS, plasma cholesterol concentration is reduced and immediate precursor concentration (7-DHC) is elevated. Surprisingly, total sterol synthesis is reduced but HMG-CoA reductase activity, a rate-limiting enzyme in cholesterol synthesis is unaltered as judged by normal urinary excretion of mevalonic acid (MVA) (Pappu, 2002)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…1). However, a recent report from Steiner’s group [14] appears to refute this possibility. They demonstrated that feeding Chol to SLOS patients reduced urinary mevalonate levels (as a result of suppression of HMG-CoA reductase (HMGR) activity by Chol), but had no significant effect on urinary MGA levels, thereby arguing against shunting to MGA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). However, a recent report from Steiner’s group [14] appears to refute this possibility. They demonstrated that feeding Chol to SLOS patients reduced urinary mevalonate levels (as a result of suppression of HMG-CoA reductase (HMGR) activity by Chol), but had no significant effect on urinary MGA levels, thereby arguing against shunting to MGA.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that feeding Chol to SLOS patients reduced urinary mevalonate levels (as a result of suppression of HMG-CoA reductase (HMGR) activity by Chol), but had no significant effect on urinary MGA levels, thereby arguing against shunting to MGA. Interestingly, this group has also found a 4- to 7-fold elevation in the levels of urinary dolichol and coenzyme Q (a.k.a., ubiquinone) [11, 14] as well as an increase in dolichol chain lengths [14] in SLOS patients, compared to controls. These findings suggested that some of the mevalonate in SLOS patients is shunted not toward leucine degradation, but rather to the nonsterol isoprenoid branches of the pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Two possible shuntways are known, the Popjak shunt linking dimethylallyl-PPi in the cholesterol biosynthesis with 3-methylcrotonyl-CoA in the Sum of 3-methylglutaric and 3-methylglutaconic acid leucine catabolism and the HMG Salvage pathway, linking 3-hydroxy-3-methylglutaryl-CoA with 3-methylglutaconylCoA. Recently we and others have shown that there is no 3-MGA-uria in a total of 27 (treated and untreated) Smith Lemli Opitz patients as well as in three patients with mevalonate kinase deficiency (Roullet et al 2012;Wortmann et al 2013b). This makes significant shunting via the mevalonate shunt as source of 3-MGA-uria unlikely.…”
Section: Discussionmentioning
confidence: 92%
“…Since cholesterol supplementation impacts serum cholesterol levels in SLOS patients (19), the treatment may have influenced the sterol-sleep relationships reported in Table 3. It is, however, reasonable to assume that at the time the sleep behavior assessments were made, serum cholesterol levels had reached a steady-state level that reflected homeostatic adaptation to cholesterol supplementation.…”
Section: Disussionmentioning
confidence: 99%